3 crucial questions about the last days - Lewis, Daniel J., 1950- (Grand Rapids, Mich. : Baker Books, 1998)
With all the discussion about the new millennium, many have a renewed interest in what will happen during the last days. This volume tackles three questions every Christian must consider when grappling with the larger issues regarding this topic. Offering a side-by-side comparison of the positions popular among evangelicals, Daniel J. Lewis provides an even-handed look at current end-times thought. The author's careful reasoning and sound interpretations of biblical passages, along with the book's brief glossary and bibliography, make this a helpful resource.
1. Are We Living in the Last Days? -- 2. Should Christians Try to Predict Christ's Return? -- 3. What Must Christians Believe about the Last Days?
Includes bibliographical references (p. 147-149) and indexes.
Keywords: End of the world